RESPONS PERTUMBUHAN BEBERAPA VARIETAS TOMAT (Lycopersicum esculentum Mill) YANG DIAPLIKASIKAN PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) DI LAHAN KERING - Maria Klara Salli; Laurensius Lehar (Partner, 2017)
The productivity of tomato plants in East Nusa Tenggara (NTT) in 2013 reached 3.43 tons/ ha or decreased 35.89% compared with 2012, this is in line with the decrease of harvested area by 2.24%. The data was also much lower compared with national production which was 15 – 16 tons/ha. Some of the possibilities that might cause a decrease in production in addition to a decrease in harvested area weredue to unsuitable planted varieties, inadequate technical culture or less efficient of pest/disease controlling.Dry land has limitations in terms of soil fertility and water availability. Physical manipulation such as the biological use of useful microbeslike rhizobacteria might be required to overcome the limitations.This research was carried out in farmers field in Penfui Village from July to November 2016. The objective of the research was to find out whether PGPR application responded to the growth of some varieties of tomatoes grown on dry land.This study uses Divided Plot Design. The main factor as the main plot was PGPR: with PGPR and without PGPR. The second factor as subplot wereTomato varieties: Tymoti F1 variety, Lentana F1 variety, Servo F1 variety, Betavila F1 variety and variety Permata F1.The results showed that PGPR application had an effect on plant growth parameters i.e. plant height 1 week after planting (WAP), 2 WAP, and 3 WAP, leaf number at 3 WAP and stem diameter at 1 WAP, 2 WAP, 3 WAP and 4 WAP as well as the number of productive branches. Keywords: Tomato varieties, plant growth, PGPR, and dry land